Dexmedetomidine reduces ventricular arrhythmias in a model of drug-induced QT-prolongation. (25th November 2020) - Frommeyer, G; Brandt, J; Ellermann, C; Wolfes, J; Eckardt, L
Abstract: Background: Dexmedetomidine is increasingly employed for conscious sedation during electrophysiological procedures. Recent experimental data have suggested direct effects of dexmedetomidine on cardiac electrophysiology. The aim of the present study was to assess the effects of dexmedetomidin on drug-induced QT-prolongation. Methods and results: In 12 isolated rabbit hearts the macrolide antibiotic erythromycin (300μM) was infused as a potent Ikr blocker after obtaining baseline data. Eight endo- and epicardial monophasic action potentials and a simultaneously recorded 12-lead ECG showed a significant prolongation of QT-interval (+25ms, p<0.05) accompanied by a moderate increase of action potential duration (APD, +5ms, p=ns) after infusion of erythromycin as compared with baseline. Effective refractory period (ERP) was also elevated (+33ms, p<0.05). Erythromycin (+26ms, p<0.05) also significantly increased spatial dispersion of repolarisation. Additional infusion of dexmedetomidine (3μM) resulted in a rather stable QT-interval (+7ms, p=ns) and APD (+7ms, p=ns) as compared with sole erythromycin treatment. Of note, a significant decrease of spatial dispersion (−24ms, p<0.05) was observed while ERP was moderately increased (+13ms, p=ns). Lowering of potassium concentration in bradycardic AV-blocked hearts resulted in the occurrence of early afterdepolarizations (EAD) and drug induced proarrhythmia with torsade de pointes in 6 of 12 erythromycin-treated hearts (40 episodes). Additional infusion of dexmedetomidine reduced the occurrence of torsade de pointes (4 of 12 hearts, 9 episodes). Conclusion: Infusion of dexmedetomidine resulted in a reduction of spatial dispersion of repolarization in the presence of a prolonged repolarization period. This resulted in a reduction of torsade de pointes with dexmedetomidine. Furthermore, an increase of ventricular refractory periods reduced inducibility of ventricular arrhythmias. Thus, in an experimental setting dexmedetomidine shows significant antiarrhythmic effects, which may influence electrophysiologic findings during clinical electrophysiologic studies. This needs to be studied in the clinical setting. Funding Acknowledgement: Type of funding source: None